Regulation of emotional memory by hydrogen sulfide: role of GluN2B‐containing NMDA receptor in the amygdala. (20th October 2014) - Wang, Can‐Ming; Yang, Yuan‐Jian; Zhang, Jie‐Ting; Liu, Jue; Guan, Xin‐Lei; Li, Ming‐Xing; Lu, Hai‐Feng; Wu, Peng‐Fei; Chen, Jian‐Guo; Wang, Fang
Abstract As an endogenous gaseous molecule, hydrogen sulfide (H2S) has attracted extensive attention because of its multiple biological effects. However, the effect of H2S on amygdala‐mediated emotional memory has not been elucidated. Here, by employing Pavlovian fear conditioning, an animal model widely used to explore the neural substrates of emotion, we determined whether H2S could regulate emotional memory. It was shown that the H2S levels in the amygdala of rats were significantly elevated after cued fear conditioning. Both intraamygdala and systemic administrations of H2S markedly enhanced amygdala‐dependent cued fear memory in rats. Moreover, it was found that H2S selectively increased the surface expression and currents of NMDA‐type glutamate receptor subunit 2B (GluN2B)‐containing NMDA receptors (NMDARs) in lateral amygdala of rats, whereas blockade of GluN2B‐containing NMDARs in lateral amygdala eliminated the effects of H2S to enhance amygdalar long‐term potentiation and cued fear memory. These results demonstrate that H2S can regulate amygdala‐dependent emotional memory by promoting the function of GluN2B‐containing NMDARs in amygdala, suggesting that H2S‐associated signaling may hold potential as a new target for the treatment of emotional disorders. <boxed-text content-type="graphic" id="jnc12961-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> In our study, the effect of hydrogen sulfide (H2S) on amygdala‐mediated emotional memory was investigated. It was found that H2S could enhance amygdala‐dependent emotional memory and long‐term potentiation (LTP) in rats by selectively increasing the function of GluN2B‐containing NMDA receptors in the amygdala. These results suggest that H2S‐associated signaling may be a new target for the treatment of emotional disorders.